2015
DOI: 10.1039/c5dt03355a
|View full text |Cite
|
Sign up to set email alerts
|

NBu4SH provides a convenient source of HS soluble in organic solution for H2S and anion-binding research

Abstract: Hydrogen sulfide (H2S) has gained significant interest within the scientific community due to its expanding roles in different (patho)physiological processes. Despite this importance, the chemical mechanisms by which H2S exerts its action remain under-scrutinized. Biomimetic investigations in organic solution offer the potential to clarify these mechanisms and to delineate the differential reactivity between H2S and HS(-). However, such studies are hampered by the lack of readily-available sources of HS(-) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…Further addition of five equivalents of NBu 4 SH regenerated the HS − host-guest complex, confirming reversible binding. Importantly, the 13 C{ 1 H} resonances of the alkyne carbons did not shift significantly (Figures 3b, d), confirming that there was no covalent modification of the receptor scaffold. Figure S15).…”
Section: Graphical Abstractsupporting
confidence: 50%
See 2 more Smart Citations
“…Further addition of five equivalents of NBu 4 SH regenerated the HS − host-guest complex, confirming reversible binding. Importantly, the 13 C{ 1 H} resonances of the alkyne carbons did not shift significantly (Figures 3b, d), confirming that there was no covalent modification of the receptor scaffold. Figure S15).…”
Section: Graphical Abstractsupporting
confidence: 50%
“…Motivated by these challenges, we report here the first examples of synthetic receptors that reversibly bind HS − using solely supramolecular interactions (Figure 1c). To investigate whether HS − is a suitable guest for hosts 1-3, we titrated NBu 4 SH [13] into 0.5-1.0 mM solution of each host in 10% DMSO-d 6 /CD 3 CN and monitored the titrations by 1H NMR spectroscopy ( Figure S1). In each case, we observed that the urea NH resonances shifted significantly downfield upon HS − addition, consistent with anion binding (Figure 2).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The sodium polysulfide salts defined were provided by Dojindo Laboratories (Munich, Germany and Kumamoto, Japan). Tetrabutyl ammonium sulfide (NBu 4 SH) was prepared as described in the literature (Hartle et al ., ). Sulfide stock solutions were prepared as previously described (Nagy et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…S32 †). 44 Such an experiment suggests that the interaction of S 2À ion with the carboxylic acid group of L2 potentially generates HS À species and anionic carboxylate group. Importantly, no change in the emission of L1 (having ester group) in presence of S 2À ion strongly support the role of free carboxylic acid in its sensing.…”
Section: Binding Modesmentioning
confidence: 99%